2018
DOI: 10.1075/lab.17072.gas
|View full text |Cite
|
Sign up to set email alerts
|

Input-output effects in the bilingual first language acquisition of English and Polish

Abstract: This diary study looks at the acquisition of early words in two bilingual sisters (0;9–2;03.22 and 0;9–1;09.13) exposed to English and Polish from birth. It examines whether their parents’ input recorded on video can explain the proportions of different types of words learnt. Their bias for social words is explained by these words being heard in isolation; that for nouns by competitive proportions of noun types heard in the input. Contrarily, the late acquisition of closed-class items is explained by their hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Are linguistic metaphors encoded in separate words with the capacity to occur in various parts of utterances (e.g., the friendship broke down; break it down ) easier to acquire than those which are always parts of other words (e.g., rozpadła , ‘broke down’)? We already know that words are prioritised for acquisition when they are presented to children individually rather than as part of longer utterances (Brent & Siskind, 2001; Gaskins, 2020). The study of metaphor acquisition could help us to determine whether a similar trend also holds for metaphorical meanings, that is, whether the acquisition of metaphorical meanings is also easier if they are introduced in single words, as opposed to parts of words that fuse several semantic and grammatical morphemes.…”
Section: Discussionmentioning
confidence: 99%
“…Are linguistic metaphors encoded in separate words with the capacity to occur in various parts of utterances (e.g., the friendship broke down; break it down ) easier to acquire than those which are always parts of other words (e.g., rozpadła , ‘broke down’)? We already know that words are prioritised for acquisition when they are presented to children individually rather than as part of longer utterances (Brent & Siskind, 2001; Gaskins, 2020). The study of metaphor acquisition could help us to determine whether a similar trend also holds for metaphorical meanings, that is, whether the acquisition of metaphorical meanings is also easier if they are introduced in single words, as opposed to parts of words that fuse several semantic and grammatical morphemes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies cited so far have mostly relied on parental reports as regards children’s HL exposure. Studies focusing on observational data include Gaskins (2020) , which found that high numbers of early verbs in two BFLA toddlers’ HL-Polish in the UK could be traced to children hearing inflected Polish verbs in isolation and at the beginning and end of utterances more frequently than their uninflected English counterparts. Gaskins and Frick (2022) suggested that early multimodal interactions with two HL speakers may facilitate early HL development.…”
Section: Introductionmentioning
confidence: 99%
“…Children tend to know many types of nouns but use each of them with low frequency counts, while they have smaller pools of verbs, adverbs, adjectives, and closed-class items but use them more frequently in speech (Goodman et al, 2008). Compare, for example, word usage frequencies in the speech of a child called Sadie with English as her main language and Polish as her heritage language (Gaskins, 2018): when video recorded for 15 h around the age of two and a half, Sadie used English nouns and adjectives on average less frequently (M = 4.49; M = 3.75) than verbs (M = 6.70), adverbs (M = 16.05), or closed-class items (M = 35.12). Fewer opportunities to use Polish than English words translated into lower usage frequencies, as in the same recordings, Sadie showed a similar average use of Polish nouns (M = 4.16), and verbs (M = 7.20), but a lower average use of Polish adjectives (0), adverbs (M = 4.25) and closed-class items (M = 3.58; Gaskins, 2018).…”
Section: Discussionmentioning
confidence: 99%